Venous Thromboembolism in Pediatric Orthopaedic Patients: Case Review. Issue 1 (January 2020) - Bishop, Courtney
Abstract : Individuals who sustain orthopaedic trauma may have an increased risk of developing a deep vein thrombosis in an injured extremity. Venous thromboembolisms (VTEs) occur rarely in the ambulatory pediatric population; however, morbidity and mortality are significant; therefore, awareness of risk factors and signs and symptoms by providers is imperative. There is limited evidence to support prophylaxis for VTE in the pediatric population, and no current guidelines exist for VTE prophylaxis in pediatric orthopaedic patients.